Growth peculiarities and age dynamics of Quercus robur L. formation in steppe region conditions - Sergey N. Kruzhilin; Sergey S. Taran; Alexandra V. Semenyutina; Elena Yu. Matvienko (Kuwait Journal of Science)
English oak (Quercus robur) is one of the main tree species in Russia’s steppic silviculture. The research investigated the growth and age dynamics of Quercus robur formations in steppe region conditions. Research was carried out in the steppe area of the Volgograd and Rostov regions in the south of Russia. Insufficient precipitation and higher temperatures in arid years has led to a decrease in shortened the growing season. and increase of difference of its continuance among species of different geographical origin. The study found regularities of growth and stand formation, variants characterized by resistance, longevity and productivity in conditions of the steppe area of Russia are developed. In conditions of dry oak stands of Quercus robur growth rates were lower than Acer platanoides and Tilia cordata. Thus, by regulating stand density, it is possible to increase the quality class of oak plantations greatly. The best results were obtained when acorns from the Buturlinovsky forest farm of Voronezh region (Shipov Forest) were used. A good companion for Quercus robur is Acer platanoides. Acer platanoides creates the second layer in an oak plantation by the age of 35-50 years. It shades the soil and prevents turf formation by making lateral shading for trees. Quercus robur favors their faster growth in height. The results of this research can be applied in forest and park architecture to improve recreational and protective plantations.